The Palaearctic types of Chrysididae (Insecta, Hymenoptera) deposited in the Linsenmaier collection. Part 2. Elampini: genus Hedychridium Abeille de Perrin, 1878 - Rosa, Paolo; Heim, René; Bernasconi, Marco Valerio (Zootaxa, 2022)
An illustrated catalogue of the Palaearctic types of species and subspecies described by Walter Linsenmaier in the genus Hedychridium Abeille de Perrin, 1878 is given. Linsenmaier described 110 species and subspecies of Hedychridium, most of the holotypes are deposited in his collection, at the Natur-Museum (Luzern, Switzerland), with the exception of 25 holotypes which are deposited at the Bristish Museum (London), at the Musée cantonal de zoologie (Lausanne) and in two private collections. Hedychridium atratum is here transferred to Chamaeholopyga Linsenmaier, 1987. Hedychridium krajniki turceyense Linsenmaier, 1968 stat. nov. is upgraded to species rank. The holotype of Hedychridium caireanum Linsenmaier, 1968 is considered lost. A list of the species described and a synthesys of his classification is given. Pictures of 83 primary and secondary types are presented.